2001
DOI: 10.1007/s004420000589
|View full text |Cite
|
Sign up to set email alerts
|

The influence of matrix habitat on Aphthona flea beetle immigration to leafy spurge patches

Abstract: Variation in movement ability by insects among different non-habitat (matrix) types may have important implications for both metapopulation dynamics and weed biocontrol practices. We used a mark-recapture experiment to explore the effects of two different matrix habitats (grass vs shrub) on the ability of two species of Aphthona (Chrysomelidae: Coleoptera) flea beetle to immigrate to patches of the invasive weed, leafy spurge. Using generalized linear models, we compared effects of the matrix habitat types, sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
53
0

Year Published

2004
2004
2014
2014

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 74 publications
(55 citation statements)
references
References 50 publications
2
53
0
Order By: Relevance
“…These data include both individuals that remained in the same fragment and those that moved between fragments within the same landscape. Thoeny, 1993;Turchin, 1998;Jonsen et al, 2001). The low number of beetles recaptured may be an artifact of the sampling method (i.e., nets do not collect all individuals in an area), but also may indicate that many ladybirds could have rapidly abandoned the landscapes.…”
Section: Discussionmentioning
confidence: 99%
“…These data include both individuals that remained in the same fragment and those that moved between fragments within the same landscape. Thoeny, 1993;Turchin, 1998;Jonsen et al, 2001). The low number of beetles recaptured may be an artifact of the sampling method (i.e., nets do not collect all individuals in an area), but also may indicate that many ladybirds could have rapidly abandoned the landscapes.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to reduced abundance of spurge in herbicide plots, plants that have survived herbicide application may provide fewer nutrients to herbivores than plants that have not experienced such a stress (Messersmith and Adkins, 1995). If A. nigriscutis is more mobile than A. lacertosa in this study area, as Jonsen et al (2001) found in similar habitat, A. nigriscutis may be more likely to abandon herbicide-controlled patches for greater resource availability elsewhere. Results of the structural equation models indicated that the relationship between previous year's spurge density and current year's relative abundance of A. lacertosa and A. nigriscutis was abolished by herbicide application that had occurred 1-2 years prior, but that the relationship was reestablished 2-3 years post-herbicide.…”
Section: Interactions Between Herbicide and Flea Beetlesmentioning
confidence: 91%
“…In that study, black beetle abundance was not found to be significantly greater than brown beetles in any vegetation type, despite the overall greater number of releases thought to consist primarily of black beetles. Jonsen et al (2001) reported significantly higher immigration probabilities for brown beetles in Canada as compared to black beetles, especially in a grassland-dominated landscape. They suggested that the larger wings of brown beetles, compared to black beetles, may play a major role in the higher dispersal patterns.…”
Section: Discussionmentioning
confidence: 99%
“…Several interacting factors probably contributed to low beetle abundance in South Dakota compared to Montana. First, infestations of leafy spurge in South Dakota were typically much smaller and more widely distributed than those found on the Montana study site, which likely reduced the potential for natural dispersal of the insects (Jonsen et al 2001). Second, because of the overall high infestation level within the Montana study site, several off-plot releases were made by landowners and managers in 1999 and 2000, increasing the probability that insects would eventually disperse into nonrelease plots.…”
Section: à2mentioning
confidence: 99%